Regional policy, convergence and subsidiarity in the European Community - Ingo P. Thomas (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
The aim of this paper is to shed light on how real income has developed across the member states and regions of the EC and to consider what demands this will place on regional policy. According to the principle of subsidiarity, a necessary, though not a sufficient, condition for EC intervention would be to prove that the scale of regional problems is too great to be handled by member states. Using two concepts of convergence, it can be shown that income convergence across the member states and even across the regions of the EC is the norm. Based on the principle of subsidiarity, policy implications concerning the assignment of a complementary function for redistributive regional policy to the EC tier are derived from the empirical evidence.
Keywords: H77; O52; R11; 330; Regionalpolitik; Subsidiaritätsprinzip; EU-Staaten; Regionale Entwicklung